2014
DOI: 10.1186/1755-8794-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dissection of psoriasis for transcriptome analyses and the post-GWAS era

Abstract: BackgroundGenome-scale studies of psoriasis have been used to identify genes of potential relevance to disease mechanisms. For many identified genes, however, the cell type mediating disease activity is uncertain, which has limited our ability to design gene functional studies based on genomic findings.MethodsWe identified differentially expressed genes (DEGs) with altered expression in psoriasis lesions (n = 216 patients), as well as candidate genes near susceptibility loci from psoriasis GWAS studies. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 87 publications
1
61
1
1
Order By: Relevance
“…A criterion of 4-fold differential expression (overexpression in SH vs. NN skin, and reduced expression in PP vs. NN skin), was selected by inspection of the plots shown in Figure S1. The expression behavior of this SG signature gene set in PP vs. NN skin was subsequently correlated with those of signature sets derived for various skin-resident cell types and keratinocytes treated with various cytokines, as described previously (Swindell et al, 2013, Swindell, Sarkar, 2015, Swindell et al, 2014). Additional details are presented in the Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
“…A criterion of 4-fold differential expression (overexpression in SH vs. NN skin, and reduced expression in PP vs. NN skin), was selected by inspection of the plots shown in Figure S1. The expression behavior of this SG signature gene set in PP vs. NN skin was subsequently correlated with those of signature sets derived for various skin-resident cell types and keratinocytes treated with various cytokines, as described previously (Swindell et al, 2013, Swindell, Sarkar, 2015, Swindell et al, 2014). Additional details are presented in the Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
“…As a final step, a Benjamini-Hochberg p-value correction is applied to generated FDR-correct p-values, accounting for the fact that the analyses was repeated with respect to many different experiments. 78 …”
Section: Methodsmentioning
confidence: 99%
“…We identified 4 independent gene expression datasets from clinical trials in psoriasis using anti-TNF (etanercept; 2 independent datasets), anti-IL-23 (guselkumab), or anti-IL-17R (brodalumab) (48)(49)(50)(51). Consistent with the gene expression results in Figure 3, in these clinical trials, GRHL3 was significantly upregulated in lesional versus nonlesional skin, and after treatment, this high level was significantly reduced to levels similar to the nonlesional controls in all but 1 etanercept trial, which still showed the correct trend (Supplemental Figure 6, A-D).…”
Section: Grhl3 Is Dispensable For Homeostatic Adult Epidermal Barriermentioning
confidence: 99%